Jews and protestants: from the reformation to the present - Aue-Ben-David, Irene; Elyada, Aya; Sluḥovsḳi, Mosheh; Wiese, Christian (De Gruyter, 2020)
Frontmatter -- Acknowledgements -- Table of Contents -- Introduction -- The Impact of the Reformation on Early Modern German Jewry -- Edom versus Edom -- Eschatology and Conversion in the Sperling Letters -- The Legacy of Anti-Judaism in Bach's Sacred Cantatas -- A New Model of Christian Interaction with the Jews -- The Vernacular Bible between Jews and Protestants -- Christian Images of the Jewish State -- Standard-bearers of Hussitism or Agents of Germanization? -- Luther's Shadow -- Exclusive Space as a Criterion for Salvation in German Protestantism during the Third Reich -- Nazi Racism, American Anti-Semitism, and Christian Duty -- Lutheran Churches and Luther's Anti-Semitism -- German Guilt and Hebrew Redemption -- List of Contributors -- Index